Oficina para o entendimento de funções matemáticas por intermédio da astronomia: aplicações no ensino médio - Amorim, Marcus Luiz Lima (2020)
This work proposes the implementation of activities in a workshop that intends to explore the content of functions in an interdisciplinary way, through contextualized themes in Astronomy more specifically related to the question of Orbits and in Physics. Thus, it seeks to contribute to the improvement of the quality of mathematics teaching and, more specifically, to the teaching of functions. This work was carried out with 29 students of the 2nd year of High School of a state school and the methodological proposal was to characterize the concept Functions in an interdisciplinary way, studying its variational character through Astronomy, addressing the concept of orbits; an experiment / prototyping related to Astronomy addressing the concept of orbits and their representations; the creation of a virtual environment and the use of GeoGebra software. Consequently, some procedures were carried out before the workshop was held: Selection of participating students, Organization of the virtual environment, Training, Development of the experiment / prototyping for simulation of the orbits surrounding massive objects, Development of the simulation and also, elaboration of the activity on function exponential / sine / cosine. Then, during the workshop the students performed activities with the experiment / prototyping and simulation and at the end of it the activity about function through GeoGebra. So, the creation of the virtual environment provided: greater interaction between teacher - student and student-student through dialogues and questions; presentation of videos, helped during the training to use GeoGebra and also in the practical classes of construction and analysis of graphs through GeoGebra. During the training using cell phones / chromebooks, several discussions were made about the concept, application and representation of function using GeoGebra and the use of the experiment / prototyping, in the workshop, allowed the practical contextualization of the concepts discussed about orbits of celestial bodies, generated countless debates on function-Mathematics-Astronomy and also aroused students' curiosity / interest in Astronomy. The educational product resulting from the work developed is a Pedagogical Notebook whose purpose is to present the path taken from planning to the execution of the workshop, with the purpose of understanding about mathematical functions in the scope of Astronomy, as well as exemplifying its use. Therefore, it is understood that the work caused significant changes in the students' conceptions of the concept of function, as they began to relate it to its aspects of variation, correspondence and dependence between variables. And, by approaching the topic through astronomical concepts, they realized that learning should contribute not only to technical knowledge, but to a broad culture.